THINKING IN THE MAKING: 3D DESIGNING AND PRINTING WITH YOUNG CHILDREN AND THE CREATION OF THRESHOLDS FOR LEARNING - Cabral, Marta; Sean, Justice (Revista Apotheke, 2022)
THINKING IN THE MAKING: 3D DESIGNING AND PRINTING WITH YOUNG CHILDREN AND THE CREATION OF THRESHOLDS FOR LEARNING